Expression and Localization of Paneth Cells and Their α-Defensins in the Small Intestine of Adult Mouse - Nakamura, Kiminori; Yokoi, Yuki; Fukaya, Rie; Ohira, Shuya; Shinozaki, Ryuga; Nishida, Takuto; Kikuchi, Mani; Ayabe, Tokiyoshi (Frontiers in Immunology, 2020)
Paneth cells contribute to intestinal innate immunity by sensing bacteria and secreting -defensin. In ICR mice, alpha-defensin termed cryptdin (Crp) in Paneth cells consists of six major isoforms, Crp1 to 6. Despite accumulating evidences that alpha-defensin functions in controlling the intestinal microbiota, topographical localization of Paneth cells in the small intestine in relation to functions of alpha-defensin remains to be determined. In this study, we examined the expression level of mRNA encoding six Crp-isoforms and Crp immunoreactivities using singly isolated crypts together with bactericidal activities of Paneth cell secretions from isolated crypts of duodenum, jejunum, and ileum. Here we showed that levels of Crp mRNAs in the single crypt ranged from 5x103 to 1x106 copies per 5 ng RNA. For each Crp isoform, the expression level in ileum was four to fifty times higher than that in duodenum and jejunum. Furthermore, immunohistochemical analysis of isolated crypts revealed that the average number of Paneth cell per crypt in the small intestine increased from proximal to distal, three to seven-fold, respectively. Both Crp1 and 4 expressed greater in ileal Paneth cells than those in duodenum or jejunum. Bactericidal activities in secretions of ileal Paneth cell exposed to bacteria were significantly higher than those of duodenum or jejunum. In germ-free mice, Crp expression in each site of the small intestine was attenuated and bactericidal activities released by ileal Paneth cells were decreased compared to those in conventional mice. Taken together, Paneth cells and their alpha-defensin in adult mouse appeared to be regulated topographically in innate immunity to control intestinal integrity.